Pathway Analysis of Behavioral Determinants in Preventing Genital Infections of Santri Putri Pondok Pesantren : Application of The Integrated Behavior Model - Ika Agustina; Kanthi Devi Ayuningtyas; Ita Noviasari (STIKes Patria Husada Blitar, 2021)
Female students who live in Islamic boarding schools are a population at risk for genital infections. The practice of personal/vaginal hygiene or menstrual hygiene is a form of maintaining reproductive health by preventing genital infections. Some bad behavior related to vaginal hygiene is a trigger factor for female genital infections. This study aimed to examine the factors behind the behavior of preventing genital infection in female students in the Islamic boarding school environment. This study was a quantitative study with a cross-sectional design. The population in this study was all female students. Determination of the sample in this study was carried out randomly with the number of subjects determined based on the rule-of-thumb sample size for path analysis, namely a minimum of 100 subjects, a minimum of 5 subjects per parameter, and a minimum of 10 subjects per variable. So that a sample of 150 female students was determined. The independent variable in this study was the behavior of preventing genital infection, while the dependent variables was: (1) behavioral intentions, (2) correct knowledge about behavior, (3) perception of the meaning of behavior, (4) environmental barriers, (5) experiential attitudes, (6) instrumental attitudes, (7) injunctive norms, (8) descriptive norms, (9) perceived behavioral control, (10) self-efficacy. This study indicated that infection prevention behavior can be determined by the behavior of female students prevention of genital infection is not influenced by the behavior of environmental barriers. Good knowledge and skills did not affect female students in taking measures to prevent genital infections; therefore, it was necessary to develop a more heterogeneous number of respondents and a questionnaire that can be understood by respondents so that an integrated behavioral model can become a reference to change behavior, and use methods that can improve their behavior.